2021
DOI: 10.1111/gcb.15900
|View full text |Cite
|
Sign up to set email alerts
|

Delayed effects of climate on vital rates lead to demographic divergence in Amazonian forest fragments

Abstract: Deforestation often results in landscapes where remaining forest habitat is highly fragmented, with remnants of different sizes embedded in an often highly contrasting matrix. Local extinction of species from individual fragments is common, but the demographic mechanisms underlying these extinctions are poorly understood. It is often hypothesized that altered environmental conditions in fragments drive declines in reproduction, recruitment, or survivorship. The Amazon basin, in addition to experiencing continu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 126 publications
(176 reference statements)
0
5
0
Order By: Relevance
“…Currently, few empirical studies have tested for the presence of TVR. However, previous studies searching for TVR have found evidence for them (Evers et al, 2021;Scott et al, 2021;Tenhumberg et al, 2018),…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Currently, few empirical studies have tested for the presence of TVR. However, previous studies searching for TVR have found evidence for them (Evers et al, 2021;Scott et al, 2021;Tenhumberg et al, 2018),…”
Section: Discussionmentioning
confidence: 92%
“…Currently, few empirical studies have tested for the presence of TVR. However, previous studies searching for TVR have found evidence for them (Evers et al, 2021; Scott et al, 2021; Tenhumberg et al, 2018), suggesting that TVR might be common. Our recent study (Evers et al, 2021) conducted a review of literature published between 1997 and 2017 and found that most demographic studies consider only a single climate timeframe: typically, the first 12 months prior to vital rate responses.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, single studies report successful results with smaller datasets. For example, a study using functional smoothing methods on a 10-year long dataset (Scott et al, 2022), and a study using a sliding-window approach (van de Pol et al, 2016) on two 15-years long individual datasets . While these results are encouraging, we did not find a similar predictive ability in our 12 datasets which were longer than 20 years.…”
Section: Discussionmentioning
confidence: 99%